ANALISIS PENCAPAIAN LABA PADA PT POS INDONESIA (PERSERO) TANJUNG REDEB (AKUNTIA JURNAL Jurnal Akuntansi, Terpercaya, Menginspirasi dan Asli, 2019)
The purpose of this study was to find out and analyze the achievement of profit targets at PT Pos Indonesia (Persero) Tanjung Redeb. The unit of analysis in this study is PT Pos Indonesia (Persero) Tanjung Redeb, having its address at Jalan Pemuda No. 542 Tanjung Redeb. The population in this study is the financial statements at PT Pos Indonesia (Persero) Tanjung Redeb since the establishment of the company in 1983 until 2017. The samples in this study are financial statements and expense reports at PT Pos Indonesia (Persero) Tanjung Redeb for the period of 2016 and 2017. Methods of data collection in this study are observation, documentation, literature study. The results of this study are that the contribution margin in 2016 was Rp 2,846,225,712 and the contribution margin ratio was 71.47%, in 2017 the contribution margin was Rp 2,683,035,593 with a contribution margin ratio of 69.41%. Degree of operating leverage in 2016 is 12.00 and 2017 is 8.00. Break event points in 2016 were Rp. 3,661,443,572 and in 2017 were Rp. 3,410,375,567. The margin of safety in 2016 was IDR 320,985,897 with the percentage being 8.06% and in 2017 the margin of safety was IDR 455,077,084 with a percentage of 11.77%. The sales target for 2016 is Rp. 3,961,944,433 and in 2017 is Rp. 3,840,010,473.